2010
DOI: 10.1680/muen.2010.163.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Performance and ownership in the governance of urban water

Abstract: In this paper the differences in terms of performance between public and the private governance in urban water management are investigated. A statistical ranking is implemented to determine programmatic efficiency differences in DEA, using an incomplete panel data that gathers information on 20 water utilities in Andalusia, in Southern Spain. In the model, labour and operational costs are considered as inputs. The volume of revenue water, the number of connections and the network length are used as outputs. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The selection of studies we have reviewed provide evidence for a mutual influence between regulation and ownership (McKay, 2003;Martínez-Espiñeira et al, 2009;García-Rubio et al, 2010). Our review suggests that the price cap rules will limit or enable funding and that access to funding drives infrastructure investment choices.…”
Section: Ownership and Riskmentioning
confidence: 95%
See 1 more Smart Citation
“…The selection of studies we have reviewed provide evidence for a mutual influence between regulation and ownership (McKay, 2003;Martínez-Espiñeira et al, 2009;García-Rubio et al, 2010). Our review suggests that the price cap rules will limit or enable funding and that access to funding drives infrastructure investment choices.…”
Section: Ownership and Riskmentioning
confidence: 95%
“…Ownership and efficiency have been widely debated internationally (Bayliss, 2003;McKay, 2003;Wallsten & Kosec, 2008;Martínez-Espiñeira et al, 2009;García-Rubio et al, 2010), and improvements to productivity and efficiency were a central consideration in pohcy decisions made by the UK govemment that led to privatization of the water companies in 1989. Emerging evidence suggests that successful privatization and efficient delivery of service is contingent on a wide range of additional factors (Saal et al, 2007;Ruester & Zschille, 2010).…”
Section: Ownership and Riskmentioning
confidence: 99%
“…Spain is a highly heterogeneous country, where climatic and regional differences emerge. Some papers have shown that, once controlled for non-controlled inputs and environmental factors, efficiency differences between private and public management tend to disappear (García-Rubio et al 2010;González-Gómez et al 2013).…”
Section: Ppps In Spanish Water Sector: Outcomesmentioning
confidence: 99%